Implementation Of Project-Based Learning To Improve Learning Outcomes Of Creative And Entrepreneurial Projects In Culinary Students At SMKN 2 Bukittinggi - Ferdi, Rohmat Aidil; Gusnita, Wiwik; Elida, Elida; Sari, Yolanda Intan (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Education is a crucial process in developing human resources that are high-quality, adaptive, and competitive. However, conventional learning methods often result in low student learning outcomes. This study aims to examine the effect of the Project-Based Learning (PjBL) model on learning outcomes in the Creative and Entrepreneurship Projects (PKK) subject for XI Culinary students at SMK Negeri 2 Bukittinggi. This research employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design involving an experimental class and a control class. The research instruments consisted of pretest and posttest assessments as well as a student response questionnaire. Data were analyzed using normality and homogeneity tests and an independent sample t-test with a significance level of 0.05. The results showed that the average posttest score of the experimental class was higher than that of the control class, with a significance value of Sig. 2-tailed = 0.00 ≤ 0.05. This indicates a significant effect of applying the PjBL model on PKK learning outcomes. Moreover, students’ responses to project-based learning were positive, with 86% strongly agreeing. Therefore, the Project-Based Learning model is effective in improving learning outcomes while providing an active, collaborative, and meaningful learning experience.